Diversidade genética, comunidade micorrízica associada e qualidade do mesocarpo de populações de Attalea speciosa Mart. ex. Spreng no estado do Maranhão - Pinheiro, Eduardo Mendonça (2023)
Babassu is a palm tree originally from Brazil that occurs sparsely in several states in the Northeast, North and Midwest regions, concentrated mainly in the state of Maranhão, occupying an area of more than 20 million hectares. It constitutes a natural resource of great importance in the Brazilian northeast and is one of the main extractive products in the country. The babassu fruit is very useful in human nutrition, especially its mesocarp, which is made up of carbohydrates, proteins, lipids and mineral salts. The objective was to relate the genetic potential of different populations of babassu in different ecological regions of the state of Maranhão from morphoagronomic characteristics, their associated soil microbiota and to proceed with the selection of babassu with greater potential for mesocarp production for the production of a nutritional supplement. agroecological. The sample areas used are located in the municipalities of Buritirana, Viana, São Luís, Cantanhede and Coroatá in the state of Maranhão. The study was carried out in natural babassu populations and the collections were carried out at the end of the dry season (October and November/2021), in which three areas per municipality and ten palm trees per area were chosen to estimate parameters related to the genetic control of the trait of plant and fruit, identification to carry out the selection of superior populations of babassu mesocarp production, spore counting of arbuscular mycorrhizal fungi and the development of a food supplement composed of babassu mesocarp flour together with the analysis of its centesimal composition for determination nutritional percentages. Babassu populations showed genetic variability. The morphological characteristics of the fruit were those that presented the highest heritability and accuracy. The city of Buritirana exhibited populations with the best productive characteristics and quality of babassu fruits. In the extraction of glomerospores, the most predominant AMF genera were Glomus and Acaulospora, especially in Cantanhede. The centesimal composition of the babassu supplement expressed a product rich in carbohydrates (up to 97%), with values of proteins above 10% and 19% of lipids